ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI GULA MERAH DI DESA BESAN KECAMATAN DAWAN KABUPATEN KLUNGKUNG - Fenrinasari, Ni Putu Dela; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
Coconut is a strategically important commodity in the lives of the Balinese people, playing social, cultural, and economic roles. Its benefits extend beyond the flesh of the fruit, which can be processed into coconut milk, copra, and coconut oil. Every part of the coconut plant has significant advantages. In the Dawan Subdistrict of Klungkung Regency, coconut trees are cultivated for sap extraction. The production of brown sugar serves as a processing industry in Klungkung Regency. However, the processing industry sector, as measured by the Gross Regional Domestic Product (GRDP), experiences fluctuations. The aim of this study was to analyze the combined effects of the number of tapped trees, raw materials, and capital on brown sugar production in Besan Village, Dawan District, Klungkung Regency. This research adopts a quantitative and associative research approach. The study was conducted in Besan Village, Dawan District, Klungkung Regency. The population consisted of all existing brown sugar craftsmen in Besan Village, and a sample of 55 ampel business units was selected as respondents. The analysis technique employed was the Cobb Douglas Production Function analysis. The results indicate that the simultaneous presence of the variables—number of tapped trees, raw materials, and capital—significantly influences brown sugar production. The partial results reveal that the number of tapped trees and raw materials have a positive and significant effect on brown sugar production, whereas capital does not impact brown sugar production. Efficiency analysis shows that the number of tapped trees has reached an efficient level, while raw materials and capital have not yet achieved efficiency. keyword : Production, Brown Sugar, Processing Industry